Biodiesel production from solid coconut waste - Sulaiman, Sarina; Abdul Raman , Abdul Aziz; Aroua, Mohamed Kheireddine (AENSI Publications, 2014)
Biodiesel is an alternative diesel fuel produced using transesterification method where edible or non edible oil and alcohol reacts in the presence of catalyst. Biodiesel is expensive than fossil fuels because of higher raw material and production costs. Solid coconut waste is an alternative raw material from waste and suitable for biodiesel production to lower the production cost. Solid coconut waste was produced after coconut milk extraction and may still contain up to 24 wt% extractable oil content. This study introduces in situ transesterification of solid coconut waste for biodiesel production with the addition of co-solvents, n-hexane and petroleum ether to improve and reduce the cost of biodiesel production. Effect of co-solvents, temperature (55- 65°C), mixing intensity (500-800 rpm), amount of n-hexane based on methanol volume (5 %, 7.5 %, 10 % and 15 %) and methanol to waste ratio (7.5:1-10:1) were studied to optimize the in situ transesterification. The highest yield was achieved at 97 % with 2.0 % of catalyst, 15 % of n-hexane, mixing of 700 rpm, 10:1 methanol to waste ratio and reaction temperature of 55°C for 3-hour.